2020
DOI: 10.1177/0300985820965554
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Lesions in Sheep Produced by Experimental Acute Clostridium Perfringens Type D Enterotoxemia

Abstract: Enterotoxemia caused by Clostridium perfringens type D is one of the most prevalent clostridial diseases of sheep. The lesions of the acute form of this disease, particularly the cerebral lesions, are well characterized; however, detailed descriptions of the cardiac and pulmonary lesions are lacking. Here we describe cardiopulmonary lesions in experimental acute type D enterotoxemia in sheep and determine the role of epsilon toxin (ETX) in the development of these lesions. Four groups of 6 sheep were intraduod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…These fine structural changes are also found in ETX-exposed pulmonary, hepatic, renal and retinal microvessels [ 43 , 57 , 58 , 59 , 60 ]. Brain microvessel endothelial damage results in the accumulation of perivascular and intramural lakes of albumin-rich, plasma protein-derived fluid ( Figure 3 ), which is typical of type D disease, and a diffusely distributed parenchymal vasogenic edema [ 15 , 61 , 62 ].…”
Section: The Acute Neurologic Syndrome: Vasculocentric Brain Injury W...mentioning
confidence: 97%
See 2 more Smart Citations
“…These fine structural changes are also found in ETX-exposed pulmonary, hepatic, renal and retinal microvessels [ 43 , 57 , 58 , 59 , 60 ]. Brain microvessel endothelial damage results in the accumulation of perivascular and intramural lakes of albumin-rich, plasma protein-derived fluid ( Figure 3 ), which is typical of type D disease, and a diffusely distributed parenchymal vasogenic edema [ 15 , 61 , 62 ].…”
Section: The Acute Neurologic Syndrome: Vasculocentric Brain Injury W...mentioning
confidence: 97%
“…However, since this gross appearance probably reflects accelerated autolysis, its diagnostic importance should not be overestimated, especially if the autopsy is delayed. There is usually scant evidence of enteritis, but segments of small intestine are sometimes distended with gas and the mucosa is hyperemic [ 16 , 22 , 23 , 42 , 43 ]. Gross findings are similar in goats and cattle.…”
Section: The Acute Neurologic Syndrome: Vasculocentric Brain Injury W...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in that case, pulmonary edema was striking and there was also red-tinged subcutaneous edema and accumulation of pink serous fluid in the thoracic cavity [ 7 ]. It was speculated that such lesions could be mediated by the action of ETX on the vascular endothelium resulting in increased vascular permeability [ 20 ]. That case also had moderate enlargement of the spleen [ 7 ].…”
Section: Gross Changesmentioning
confidence: 99%
“…In laboratory animal models and natural disease hosts, epsilon-toxin (ETX) plays a critical role in the virulence of Clostridium perfringens type D strains and, likely, type B strains ( 1 4 ). Our 2011 mBio paper ( 5 ) reported that an agrB null mutant of type D strain CN3718 grew similarly in tryptone-glucose-yeast extract (TGY) broth to its wild-type parent, but produced less ETX, and that this effect was partially reversible by complementation.…”
Section: Introductionmentioning
confidence: 99%